The Role of Authentic Local Resources and Social Capital in the Development of Sustainable Village Tourism - Sukaris Sukaris (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2024)
This study aims to determine the role of authentic local resources and social capital in influencing the development of sustainable village tourism. This research refers to the social exchange theory and the theory of resources base view, using 30 managers of the village tourism "Lontar Sewu" as respondents who then carried out a bootstrapping process of 300 data. WarpPLS processed the collected data. The results revealed that the data collected met the validity and reliability requirements and the fit of the model. Estimation of the model showed that the authenticity of local resources and the social capital of the community had a positive relationship with sustainable village tourism. Likewise, the verification showed that the authenticity of local resources affected sustainable village tourism, and social capital affected sustainable village tourism. The findings showed that the authenticity of local resources and social capital was proven to have an important role in sustainable village tourism, such as the sustainability of the Lontar tree ecosystem (authenticity), the uniqueness of village tourism that is maintained, and local wisdom that makes the community involved in developing village tourism. This research provides a significant theoretical contribution to the sustainable tourism literature. Furthermore, this research has a number of practical implications for village tourism managers in terms of sustainable village tourism management.